The Moderating Role Institutional Ownership and Tax Planning in Earning Management - Chaironisa, Zulaepa; Suryanti, Heni (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to examine and analyze the role of institutional ownership and tax planning in earnings management. The source of research data is secondary data in the form of financial statements. The study population is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The sampling technique is purposive sampling. The financial statements analyzed amounted to 190 financial statements from 38 companies according to and qualified research samples. This study used quantitative descriptive analysis method using SEM-PLS analysis and processed using Warppls 8.0. The results showed that tax planning had a significant effect on earnings management and institutional ownership was able to moderate the relationship between tax planning and earnings management.